2012
DOI: 10.1155/2012/691369
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Patients with Chronic Kidney Disease

Abstract: Metabolic syndrome and its components are associated with chronic kidney disease (CKD) development. Insulin resistance (IR) plays a central role in the metabolic syndrome and is associated with increased risk for CKD in nondiabetic patients. IR is common in patients with mild-to-moderate stage CKD, even when the glomerular filtration rate is within the normal range. IR, along with oxidative stress and inflammation, also promotes kidney disease. In patients with end stage renal disease, IR is an independent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
117
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 138 publications
3
117
0
2
Order By: Relevance
“…This indicates that the uremic condition might reduce the RBC-NOS response to these stimuli possibly due to biochemical or metabolic alterations such as increased insulin resistance [44]. As mentioned above, in our study, we found that basal RBC-NOS was significantly more activated in uremic erythrocytes than in controls.…”
Section: Discussionsupporting
confidence: 77%
“…This indicates that the uremic condition might reduce the RBC-NOS response to these stimuli possibly due to biochemical or metabolic alterations such as increased insulin resistance [44]. As mentioned above, in our study, we found that basal RBC-NOS was significantly more activated in uremic erythrocytes than in controls.…”
Section: Discussionsupporting
confidence: 77%
“…This discrepancy between our results and previous studies (29) may be due to treatment of type 2 DM. Renal dysfunction promotes insulin resistance in patients with mild to moderate stage of CKD, even when eGFR is maintained within the normal range (30). In addition, insulin resistance is associated with increased risk for CKD and is an independent predictor of cardiovascular diseases (30).…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction promotes insulin resistance in patients with mild to moderate stage of CKD, even when eGFR is maintained within the normal range (30). In addition, insulin resistance is associated with increased risk for CKD and is an independent predictor of cardiovascular diseases (30). Therefore, annual screening for type 2 DM is recommended for all CKD subjects (31).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with end-stage renal disease, IR is an independent predictor of CV disease and is linked to protein energy wasting and malnutrition. 23 Nutritional, metabolic, and CV complications of renal disease may be a consequence of abnormal insulin action. Systemic inflammation, oxidative stress, elevated serum adipokine and fetuin-A, metabolic acidosis, vit D deficiency, depressed serum erythropoietin, endoplasmic reticulum stress, and suppressors of cytokine signaling all cause IR by suppressing insulin receptor-PI3K-Akt pathways in CKD.…”
Section: Introductionmentioning
confidence: 99%